2007
DOI: 10.1007/s10195-007-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peritrochanteric fractures with the Endovis BA cephalomedullary nail: multicenter study of 1091 patients

Abstract: Treatment of peritrochanteric fractures involves reduction and synthesis using reconstruction plates and screws, intramedullary or cephalomedullary nails, or external fixators. A new cephalomedullary nail, Endovis BA (Citieffe, Italy), made of titanium alloy implanted without reaming and is fixed with 2 cephalic screws was used to treat 1091 patients with lateral fractures of the femoral neck (AO class 31-A). The patients had a mean age of 75 years (range, 48-99 years), and 83% had one or more systemic comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The preoperative choice of length depends on the distal extent of the fracture. A medium-length nail allows easier insertion than a long nail and distal locking in combination with a targeting jig [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The preoperative choice of length depends on the distal extent of the fracture. A medium-length nail allows easier insertion than a long nail and distal locking in combination with a targeting jig [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it must be stressed that, with Endovis BA the same key features that proved successful with Endovis were emphasized and improved with the state-of-the-art production technologies and materials. Overall, Endovis BA evolved toward higher patient tolerability while maintaining safety and improving effectiveness [5].…”
Section: Dear Editormentioning
confidence: 99%
“…• Dimensions -Endovis BA is about 15% smaller.Nevertheless, it must be stressed that, with Endovis BA the same key features that proved successful with Endovis were emphasized and improved with the state-of-the-art production technologies and materials. Overall, Endovis BA evolved toward higher patient tolerability while maintaining safety and improving effectiveness [5].The study we documented in the referred paper [1] was performed using Endovis BA nail (in the period 2007-2009). Hopefully, on the basis of the additional information provided here (which is not anyhow influencing the study's results), perspective readers will be able to adapt the issues faced in the discussion and conclusion sections to Endovis BA rather than to Endovis.…”
mentioning
confidence: 99%
“…The Endovis® proximal femoral nail (EN) has been designed by Citieffe® (Italy) to solve the problems associated with the use of intramedullary fixation devices. Some studies have demonstrated a good outcome with few complications after treatment with this intramedullary femoral nail [9,10]. EN is made of a titanium alloy with a cervicodiaphyseal angle of 130 degrees, a metaphyseal angle of 5 degrees and a total length of 195 mm (standard nail) or 220 mm (medium nail).…”
Section: Introductionmentioning
confidence: 99%